A skin-care soft nonwoven fabric and disposable sanitary products using the nonwoven fabric

By preparing softeners containing metal-doped fullerene masterbatches and fullerene grafted sulfonate anions, combined with ES fiber hydrophilic oil agents, soft non-woven fabrics are prepared for disposable sanitary products, the skin problems caused by these products during use are solved, and the dual effects of skin care and durability are achieved.

CN115896968BActive Publication Date: 2025-04-11FUJIAN HENGAN HLDG CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211663676.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-04-11
Estimated Expiration
2042-12-23

AI Technical Summary

Technical Problem

Disposable sanitary products such as diapers and sanitary napkins can easily cause skin problems when used.

Method used

Using the preparation method of skin care soft non-woven fabrics, ES fibers and non-woven fabrics are prepared by preparing metal-doped fullerene masterbatches and fullerene grafting sulfonate anions, combined with ES fiber hydrophilic oil agents, ES fibers and non-woven fabrics are prepared through spinning process to make the surface layer of disposable sanitary products.

Benefits of technology

Through the synergistic elimination of free radicals by fullerene, skin care functions are achieved, skin problems are reduced, and fiber adhesion is improved through the van der Waals force interaction of fibers, enhancing the softness and durability of non-woven fabrics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115896968B_ABST
    Figure CN115896968B_ABST
Patent Text Reader

Abstract

The invention discloses a skin-care soft non-woven fabric and a disposable sanitary product using the non-woven fabric. The method comprises: preparing a master batch containing metal doped fullerenes; preparing a softener containing sulfonate anions grafted with fullerenes; adding the prepared softener containing sulfonate anions grafted with fullerenes into an ES fiber hydrophilic oil agent, and preparing ES fibers through a spinning process by using the master batch containing metal doped fullerenes and the ES fiber hydrophilic oil agent. The invention utilizes the sulfonate anion group to be adsorbed on the fiber surface of the positively charged metal doped fullerene master batch, and at the same time, the long carbon chain in the softener interacts with the fiber through van der Waals force, thereby solving the problem of fullerene adhesion on the fiber. The synergistic free radical elimination effect of two fullerenes in different addition forms is utilized to achieve the skin care function, thereby reducing skin problems. The fullerene in the fiber spinning oil agent absorbs the free radicals of the skin and then transfers to the fullerene fiber master batch, thereby achieving a long-term free radical elimination effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a skin-care soft nonwoven fabric and a disposable sanitary product using the nonwoven fabric Background Art

[0002] Disposable sanitary products such as diapers and sanitary napkins can easily cause skin problems when worn. Summary of the invention

[0003] To solve the above problems, the object of the present invention is to provide a soft nonwoven fabric for skin care.

[0004] To achieve the above object, the method for preparing the skin-protecting soft nonwoven fabric of the present invention comprises the following steps:

[0005] preparing metal-doped fullerene masterbatch;

[0006] Preparation of fullerene-grafted softener containing sulfonate anion;

[0007] The prepared fullerene-grafted softener containing sulfonate anions is added into the ES fiber hydrophilic oil agent in an amount of 1-10%.

[0008] ES fibers are prepared by spinning process using metal-doped fullerene masterbatch and ES fiber hydrophilic oil agent;

[0009] The ES fibers were used to prepare nonwoven fabrics.

[0010] Furthermore, the step of preparing the metal-doped fullerene masterbatch comprises:

[0011] Metal-doped fullerenes were prepared by arc discharge method;

[0012] The metal-doped fullerene, polyethylene resin and dispersant are uniformly mixed at high speed, and melt-extruded and granulated in a twin-screw extruder to obtain the metal-doped fullerene masterbatch.

[0013] Furthermore, the step of preparing the fullerene-grafted softener containing sulfonate anions comprises:

[0014] In the C60 or C70 fullerene benzene solution, KOH solution and tetrabutylammonium hydroxide as a phase transfer catalyst are added, and then H 2 O 2 After reacting for 12 hours at room temperature, the aqueous solution changes from colorless to brown-yellow, and the benzene solution changes from purple to colorless. Phase separation is performed using a separatory funnel to obtain a dark brown hydroxylated fullerene solution, which is then centrifuged and purified by adding methanol, and then dried in vacuum to obtain hydroxylated fullerene;

[0015] The hydroxylated fullerene is reacted with (9Z)-9-octadecenoic acid, aminosulfonic acid and diethyl sulfate to prepare a fullerene-grafted softener containing sulfonate anions.

[0016] To achieve the above-mentioned purpose, the disposable sanitary product of the present invention comprises a surface layer, a composite diffusion and flow guiding layer, an absorbent core and a bottom layer;

[0017] The surface layer is made of one or more layers of non-woven fabrics prepared by the above-mentioned method for preparing the skin-care soft non-woven fabric;

[0018] The composite diffusion guide layer is a three-layer diffusion guide layer, wherein the surface layer is a non-woven fabric formed by heat bonding after fiber combing into a web, the pore size of the non-woven fabric is 0.2-4.5mm, and the square gram weight is 10-45g / m 2 ;

[0019] The middle layer is a spunlace nonwoven fabric, which is composed of two components: viscose fiber and polyester fiber, wherein the content of viscose fiber is 30-95%;

[0020] The lower layer is spunlace nonwoven fabric;

[0021] The thickness of the middle spunlace nonwoven fabric is greater than or equal to the thickness of the lower spunlace nonwoven fabric, the density of the middle spunlace nonwoven fabric is less than or equal to the density of the lower spunlace nonwoven fabric, the pore size of the middle spunlace nonwoven fabric is greater than or equal to twice the pore size of the lower spunlace nonwoven fabric, and the diameter of the polyester fiber in the middle spunlace nonwoven fabric is greater than or equal to the diameter of the lower spunlace nonwoven fabric;

[0022] The absorbent core comprises at least one layer of dust-free paper, and the dust-free paper layer is composed of a plurality of dust-free paper rows arranged along the length direction;

[0023] The bottom layer is a biaxially stretched antibacterial breathable film.

[0024] Furthermore, the disposable sanitary product is also provided with antibacterial soft anti-powdering dust-free paper, and the method for preparing the antibacterial soft anti-powdering dust-free paper comprises the following steps:

[0025] The chlorinated fatty alkyl dimethyl tertiary amine is reacted with benzyl chloride to prepare chlorinated fatty alkyl dimethyl benzyl ammonium chloride;

[0026] Polyamide epichlorohydrin resin is prepared using diethylenetriamine, adipic acid and epichlorohydrin chloride as raw materials;

[0027] The prepared chlorinated fatty alkyl dimethyl benzyl ammonium chloride is added into the prepared polyamide epichlorohydrin resin to prepare an antibacterial, soft and anti-powdering resin;

[0028] The prepared antibacterial, soft and anti-powdering resin is sprayed on the surface of the combed fluff pulp and ES fiber web, and then reinforced with hot air to obtain dust-free paper with antibacterial activity.

[0029] The present invention utilizes sulfonate anion groups to be adsorbed on the fiber surface of the positively charged metal-doped fullerene masterbatch, and at the same time, the long carbon chain in the softener interacts with the fiber through van der Waals force, thereby solving the problem of fullerene adhering to the fiber. The two fullerenes in different addition forms are utilized to synergistically eliminate free radicals, thereby achieving skin care function and reducing skin problems. The fullerene in the fiber spinning oil absorbs free radicals from the skin and then transfers to the fullerene fiber masterbatch, thereby achieving a long-term free radical elimination effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the reaction formula for preparing polyamide epichlorohydrin resin in the embodiment of the present invention.

[0031] Figure 2 This is the reaction formula for preparing the antibacterial, soft and anti-powdering resin in the embodiment of the present invention. DETAILED DESCRIPTION

[0032] The method for preparing the soft skin-care nonwoven fabric of the present invention comprises the following steps:

[0033] Preparation of metal-doped fullerene masterbatch: metal-doped fullerene, polyethylene resin, and dispersant (polyethylene wax and stearic acid) are uniformly mixed at high speed, and melt-extruded and granulated in a twin-screw extruder to obtain metal-doped fullerene masterbatch.

[0034] Preparation of fullerene grafted softener containing sulfonate anion; Fullerene (C60, C70) is hydroxylated. In C60 or C70 benzene solution, KOH solution is added, tetrabutylammonium hydroxide is used as a phase transfer catalyst, and then H2O2 is added to react at room temperature for 12 hours. The aqueous solution changes from colorless to brownish yellow, and the benzene solution changes from purple to colorless. Phase separation is performed using a separatory funnel to obtain a dark brown hydroxylated fullerene solution, methanol is added for centrifugal purification, and vacuum drying is performed to obtain the hydroxylated fullerene.

[0035] Fullerene grafted quaternary ammonium anion softener, hydroxylated fullerene and (9Z)-9-octadecenoic acid, aminosulfonic acid, diethyl sulfate are reacted to prepare a fullerene grafted softener containing sulfonate anions.

[0036] Preparation of ES fiber oil: add fullerene grafted quaternary ammonium anion softener into conventional ES fiber hydrophilic oil, the added amount is 1-10%, and apply it to ES fiber.

[0037] ES fibers are prepared by spinning process using metal-doped fullerene masterbatch and ES fiber hydrophilic oil agent.

[0038] Example

[0039] Preparation of metal-doped fullerene masterbatch: 18 parts of metal-doped fullerene, 80 parts of polyethylene resin, and 2 parts of dispersant (polyethylene wax and stearic acid) are uniformly mixed at high speed, and melt-extruded and granulated in a twin-screw extruder to obtain metal-doped fullerene masterbatch.

[0040] Preparation of fullerene grafted softener containing sulfonate anion: Fullerene (C60, C70) was hydroxylated. In 100 mL of 2 mg / mL C60 or C70 benzene solution, 2 mL of 1 mol / L KOH solution was added, 8 drops of 10% tetrabutylammonium hydroxide as a phase transfer catalyst, and then 3 mL of 30% H 2 O 2 After reacting for 12 hours at room temperature, the aqueous solution changes from colorless to brown-yellow, and the benzene solution changes from purple to colorless. Phase separation is performed using a separatory funnel to obtain a dark brown hydroxylated fullerene solution, which is then centrifuged and purified by adding methanol, and then dried in vacuum to obtain hydroxylated fullerene.

[0041] The fullerene grafted sulfonate anion softener is prepared by reacting 1 part of hydroxylated fullerene with 1 part of (9Z)-9-octadecenoic acid, 1 part of aminosulfonic acid and 1 part of diethyl sulfate to prepare the fullerene grafted sulfonate anion-containing softener.

[0042] Preparation of ES fiber oil: 10% fullerene grafted quaternary ammonium anion softener was added to conventional ES fiber hydrophilic oil and applied to ES fiber.

[0043] ES fibers are prepared by spinning process using metal-doped fullerene masterbatch and ES fiber hydrophilic oil. In the above method, sulfonate anion groups are adsorbed on the fiber surface of positively charged metal-doped fullerene masterbatch, and the long carbon chain in the softener interacts with the fiber through van der Waals force, solving the problem of fullerene adhesion on the fiber.

[0044] The two fullerenes in different addition forms are used to synergistically eliminate free radicals to achieve skin care functions, thereby reducing skin problems. The fullerenes in the fiber spinning oil absorb the free radicals of the skin and transfer them to the fullerene fiber masterbatch to achieve a long-term free radical elimination effect.

[0045] Test method:

[0046] 1. Diaper pretreatment: Test according to the permeability test method of code L in Appendix A of GB / T 28004.1-2022

[0047] 2. A quantitative DPPH load was fixed on artificial skin to simulate free radicals on human skin. The artificial skin was attached to the surface of the diaper that had been tested for permeability performance and was placed in a dark place at 25°C for 30 minutes.

[0048] 3. Place the artificial skin after the test into an excess of vitamin C solution for full reaction, and calculate the DPPH clearance rate based on the remaining vitamin C in the test solution.

[0049] The test plan and results are shown in the table below.

[0050]

[0051] Through the above test comparison, it can be seen that the DPPH elimination rate in the solution of adding the fullerene-grafted quaternary ammonium anion softener of the present invention into the fiber spinning oil + ES fiber containing fullerene masterbatch reaches 99%.

[0052] As an embodiment of the present invention, the disposable sanitary product of the present invention can be a sanitary napkin or a diaper. The disposable sanitary product of the present invention comprises a surface layer, a composite diffusion and flow-guiding layer, an absorbent core and a bottom layer;

[0053] The surface layer is made of one or more layers of non-woven fabrics prepared by the above-mentioned method for preparing the skin-care soft non-woven fabric;

[0054] The composite diffusion guide layer is a three-layer diffusion guide layer. The surface layer uses a double-component fiber with a length of 50 mm and a thickness of 25 denier, which has been subjected to multiple hydrophilic treatments. The double components are polyethylene and polyester. The surface fibers are combed into a web and then thermally bonded into a non-woven fabric. The pore size of the non-woven fabric is 2.5 mm and the square gram weight is 25 g / m 2 ;

[0055] The middle layer is a spunlace nonwoven fabric, which is composed of two components, viscose fiber and polyester fiber, wherein the content of viscose fiber is 45%; the lower layer is also a spunlace nonwoven fabric, but the middle and lower layers of the spunlace nonwoven fabric differ in thickness, density, pore size, porosity, polyester fiber thickness and material composition ratio; wherein the thickness of the middle layer of the spunlace nonwoven fabric is greater than or equal to the thickness of the lower layer of the spunlace nonwoven fabric, the density of the middle layer of the spunlace nonwoven fabric is less than or equal to the density of the lower layer of the spunlace nonwoven fabric, the pore size of the middle layer of the spunlace nonwoven fabric is greater than or equal to 2 times the pore size of the lower layer of the spunlace nonwoven fabric, and the diameter of the polyester fiber in the middle layer of the spunlace nonwoven fabric is greater than or equal to the diameter of the lower layer of the spunlace nonwoven fabric. The above structure forms a funnel-shaped liquid transmission structure between the upper and lower layers, and there is a potential energy difference between the upper and lower layers, which facilitates rapid infiltration and rapid diffusion of the liquid; the above layers are bonded with wet-strength hot melt adhesive; wherein the wet-strength hot melt adhesive is Henkel 5811u; gluing method is Omega spray glue.

[0056] The absorbent core comprises at least one layer of dust-free paper, and the dust-free paper layer is composed of a plurality of dust-free paper rows arranged along the length direction;

[0057] The bottom layer is a biaxially stretched antibacterial breathable film, for example, a biaxially stretched antibacterial breathable film added with nano-silver can be used.

[0058] The above-mentioned dust-free paper array is formed by rolling or folding one or more layers of antibacterial soft anti-powdering dust-free paper. The preparation method of the antibacterial soft anti-powdering dust-free paper comprises the following steps:

[0059] The chlorinated fatty alkyl dimethyl tertiary amine is reacted with benzyl chloride to prepare chlorinated fatty alkyl dimethyl benzyl ammonium chloride;

[0060] Polyamide epichlorohydrin resin is prepared using diethylenetriamine, adipic acid and epichlorohydrin chloride as raw materials;

[0061] The prepared chlorinated fatty alkyl dimethyl benzyl ammonium chloride is added into the prepared polyamide epichlorohydrin resin to prepare an antibacterial, soft and anti-powdering resin;

[0062] The prepared antibacterial, soft and anti-powdering resin is sprayed on the surface of the combed fluff pulp and ES fiber web, and then reinforced with hot air to obtain dust-free paper with antibacterial activity.

[0063] Example

[0064] 1 mol of chlorinated fatty alkyl dimethyl tertiary amine is reacted with 1 mol of benzyl chloride to prepare chlorinated fatty alkyl dimethyl benzyl ammonium chloride;

[0065] 1.02 mol of diethylenetriamine and 1 mol of adipic acid were reacted to form prepolymer PA, and 1 mol of chloro-epichlorohydrin was used as raw material to prepare polyamide epichlorohydrin resin with a solid content of 12.5%;

[0066] The prepared chlorinated fatty alkyl dimethyl benzyl ammonium chloride is added to the prepared polyamide epichlorohydrin resin to prepare an antibacterial, soft and anti-powdering resin;

[0067] The prepared antibacterial, soft and anti-powdering resin was sprayed on the surface of the combed fluff pulp and ES fiber web (the spraying amount was 10 g / M 2 ), and then hot air reinforced to produce dust-free paper with antibacterial activity.

[0068] In the present invention, the chlorine replaces the electron-withdrawing group so that the cationic charge of the ammonium group on the polyamide epichlorohydrin resin is greater than the cationic charge of the ammonium group of benzalkonium chloride. The ammonium group of the polyamide epichlorohydrin resin is adsorbed on the fluff pulp fiber, while the ammonium group of benzalkonium chloride is away from the fluff pulp fiber, so that the ammonium group is exposed and exerts antibacterial activity.

[0069] Conventional dust-free paper has poor adhesion between fluff pulp, so when used in the production of sanitary napkins and diapers, powder will fall off, and the machine needs to be cleaned frequently, affecting production efficiency, otherwise the product will be dirty. However, due to the self-crosslinking network structure of the present invention, it has multiple binding sites, which can ensure close bonding with the fluff pulp without falling off. The combination of resin and fluff pulp can fix the fluff pulp, thereby preventing powder from falling off. At the same time, the long-chain alkyl group has good softness, which can improve the softness of dust-free paper.

[0070] test

[0071] 1. Quaternary ammonium salt dissolution test: Take 5g of antibacterial dust-free paper treated with antibacterial agents, cut it into pieces and put it into 100mL of deionized water for ultrasonic treatment for 10 minutes, filter it, and test the nitrogen content in the filtrate according to "HJ 616-2012 Determination of total nitrogen in water quality - alkaline potassium persulfate digestion ultraviolet spectrophotometry". The blank sample is dust-free paper without antibacterial treatment, and the control sample is dust-free paper directly sprayed with benzalkonium chloride.

[0072] Blank Experimental Sample Control Nitrogen concentration / mg / L 0.2 0.3 9.8

[0073] 2. Determination of the bactericidal performance of dust-free paper: Test the bactericidal performance of dust-free paper according to C3 in GB 15979

[0074]

[0075]

[0076] 3. Test of diaper permeability: Test according to Appendix A of GB / T 28004.1-2021 Diapers Part 1: Baby Diapers

[0077]

[0078] 4. Powder loss rate test: Test according to Appendix B of GB / T 20808-2022 Paper Towels

[0079] Blank Experimental Sample Control Powder loss rate / % 1.8 0.3 1.5

[0080] 5. Softness test: Tested in accordance with GB / T 8942-2016 Determination of paper softness

[0081]

[0082] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.

[0083] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a skin-care soft nonwoven fabric, characterized in that: The method comprises the following steps: preparing metal-doped fullerene masterbatch; Preparation of fullerene-grafted softener containing sulfonate anion; Adding the prepared fullerene-grafted softener containing sulfonate anions into the ES fiber hydrophilic oil agent in an amount of 1-10%; ES fibers are prepared by spinning process using metal-doped fullerene masterbatch and ES fiber hydrophilic oil agent; Using ES fibers to prepare nonwoven fabrics; The steps of preparing the fullerene-grafted softener containing sulfonate anions include: In the C60 or C70 fullerene benzene solution, KOH solution and tetrabutylammonium hydroxide as a phase transfer catalyst are added, and then H2O2 is added to react at room temperature for 12 hours, the aqueous solution changes from colorless to brown-yellow, and the benzene solution changes from purple to colorless; phase separation is performed using a separatory funnel to obtain a dark brown hydroxylated fullerene solution, methanol is added for centrifugal purification, and vacuum drying is performed to obtain hydroxylated fullerene; The hydroxylated fullerene is reacted with (9Z)-9-octadecenoic acid, aminosulfonic acid and diethyl sulfate to prepare a fullerene-grafted softener containing sulfonate anions.

2. The method for preparing the skin-care soft nonwoven fabric according to claim 1, characterized in that: The step of preparing the metal-doped fullerene masterbatch comprises: Metal-doped fullerenes were prepared by arc discharge method; The metal-doped fullerene, polyethylene resin and dispersant are uniformly mixed at high speed, and melt-extruded and granulated in a twin-screw extruder to obtain the metal-doped fullerene masterbatch.

3. A disposable sanitary product, comprising a surface layer, a composite diffusion and flow-guiding layer, an absorbent core and a bottom layer, characterized in that: The surface layer is made of one or more layers of non-woven fabrics prepared by the method for preparing the skin-care soft non-woven fabric according to claim 1; The composite diffusion guide layer is a three-layer diffusion guide layer, wherein the surface layer is a non-woven fabric formed by heat bonding after fiber combing into a web, the pore size of the non-woven fabric is 0.2-4.5mm, and the square gram weight is 10-45g / m 2 ; The middle layer is a spunlace nonwoven fabric, which is composed of two components: viscose fiber and polyester fiber, wherein the content of viscose fiber is 30-95%; The lower layer is spunlace nonwoven fabric; The thickness of the middle spunlace nonwoven fabric is greater than or equal to the thickness of the lower spunlace nonwoven fabric, the density of the middle spunlace nonwoven fabric is less than or equal to the density of the lower spunlace nonwoven fabric, the pore size of the middle spunlace nonwoven fabric is greater than or equal to twice the pore size of the lower spunlace nonwoven fabric, and the diameter of the polyester fiber in the middle spunlace nonwoven fabric is greater than or equal to the diameter of the lower spunlace nonwoven fabric; The absorbent core comprises at least one dust-free paper layer, and the dust-free paper layer is composed of a plurality of dust-free paper rows arranged along the length direction; The bottom layer is a biaxially stretched antibacterial breathable film.

4. The disposable sanitary product according to claim 3, characterized in that: The dust-free paper is sprayed with antibacterial, soft and anti-powdering resin.

Citation Information

Patent Citations

  • Dry and clean high-adsorption hot-air non-woven fabric

    CN108049029A

  • Dry-comfortable side-leakage-prevention hygienic product surface layer and processing technology thereof

    CN108859310A